Sex and Gender in Natural Language - Percival, W. Keith (Kansas Working Papers in Linguistics, 1981)
The topic of this paper is the relation between a real-world category (sex) and a linguistic category (gender). In the first part, the gender system of Indo-European languages is discussed. Then the gender-system in a language without grammatical gender is described. Finally, a few general comments are hazarded on the difficult question of the relation between sex and gender. The paper closes with a discussion of recent puristic efforts by the feminist movement in the U.S. to rid English of what are termed sexist words.